Oxidative and membrane stress-mediated antibacterial activity of WS2 and rGO-WS2 nanosheets - Navale, Govinda R.; Rout, Chandra Sekhar; Gohil, Kushal N.; Dharne, Mahesh S.; Late, Dattatray J.; Shinde, Sandip S. (RSC Advances, 2015)
Graphene-based materials have strong cytotoxic attributes against bacteria due to their unique physicochemical properties. We examined the antibacterial activities of nanosheets of the graphene analogue tungsten disulphide (WS2) and a composite of reduced graphene oxide-tungsten disulphide (rGO-WS2), comparing them with reduced graphene oxide (rGO) by a time and concentration dependent viability assay and growth curve studies against four bacterial strains: Gram negative Escherichia coli (E. coli) and Salmonella typhimurium (S. typhimurium), and Gram positive Bacillus subtilis (B. subtilis) and Staphylococcus epidermidis (S. epidermidis). The nanosheets of the rGO-WS2 composite caused a more significant retardation in bacterial growth and inhibitory effect on the tested bacterial strains than WS2, followed by rGO. The tested E. coli and B. subtilis strains were more susceptible than the other strains. A mechanistic study revealed that rGO and WS2 did not produce the superoxide anion (O-2(-)) or reactive oxygen species (ROS), but the nanocomposite of rGO-WS2 did produce both. However, all these materials did oxidize glutathione, which serves as a redox state mediator in bacteria. We conclude that the antimicrobial mechanism is due to the combined effect of initial cell deposition on the rGO-WS2 materials, the membrane stress due to direct contact with the nanosheets, and the produced superoxide anion-independent oxidation mechanisms. The beneficial aspects of the physicochemical properties of rGO-WS2, such as its size and conductivity, can be precisely customized to reduce its health and environmental risk factors.

One-pot bioconversion of tomato waste into poly-gamma-glutamic acid (gamma-PGA) biopolymer by a novel biocatalyst - Nair, Pranav G.; Joseph, Emmanuel; Killi, Naresh; Konchada, Sravanya; Nisal, Anuya; Gundloori, Rathna Venkata Naga; Dharne, Mahesh S. (ACS Sustainable Chemistry & Engineering, 2021)
Landfilling of rotten tomatoes can lead to environmental instability and a huge economic loss to the producers. This letter reports an effective valorization of tomato waste into a promising biopolymer, i.e., poly-gamma-glutamic acid (gamma-PGA) by a novel biocatalyst Bacillus paralicheniformis NCIM 5769. The gamma-PGA is one of the most expensive biopolymers with multifarious applications in wound healing, drug delivery, and regenerative medicine fields. However, its adoption into various applications is finite due to its exorbitant production cost. Herein, rotten tomatoes (without additional nutrient supplementation) served as the chassis for the fermentative production of 40 g/L of highly pure gamma-PGA within 48 h at ambient temperature. Further, NMR, DSC, and TGA confirmed the purity of synthesized gamma-PGA identical to standard gamma-PGA. This process has potential in the commercialization of.-PGA by significantly reducing the production cost, followed by the effective utilization of tomato waste leading to United Nations Sustainable Development Goal 12 (i.e., ensure sustainable consumption and production patterns).
Keywords: Commercialization; Poly-gamma-glutamic acid; Rotten tomatoes; United Nations Sustainable Development Goals; Waste utilization